Faint LAEs near z > 4.7 C IV absorbers revealed by MUSE - Diaz, Carlos Gonzalo (2021)
We present the results from the search for Lyman Alpha emitters (LAEs) in the proximity of 11 civ absorption systems at $z>4.7$ in the spectrum of the QSO J1030+0524, using data from MUSE.We have found multiple LAE candidates close to four civ systems at $z_{extciv}=4.94$--5.74 with $log_{10}(N_{extciv}[$cm$])>13.5$. At $z=5$--6, civ systems with W$_0(extciv)> 0.2$ AA seem more likely to have galaxies with Lya emission within $ho< 200$ proper kpc (4/5 cases), than the civ systems with W$_0(extciv)<0.2$ AA (0/6 cases). The impact parameter of LAE-civ systems with equivalent widths $W_0($civ$) > 0.5$ AA is in the range $11, simlt,ho,simlt,200$ proper kpc (pkpc). Furthermore, all candidates are in the luminosity range0.18--1.15 L$^{star}_{extLya}(z=5.7)$, indicating that the environment of civ systems within 200 pkpc is populated by the faint end of the Lya luminosity function. We report a 0.28,L$^{star}_{extLya}$ galaxy at a separation of $ho=11$ pkpc from a strong civ absorption ($log_{10}(N_{extciv}[$cm$])=14.52$) at $z_{extciv}=5.72419$. The prevalence of sub-L$^{star}_{extLya}$ galaxies in the proximity of $z>4.9$ civ systemssuggest that the absorbing material is rather young, likely ejected in the recent past of the identified galaxies. The connection between faint LAEs and high-ionization absorption systems reported in this work, is potentially a consequence of the role of low mass galaxies in the early evolution of the circum-galactic and intergalactic media.